Inequalities in eating behaviour of 11- 15 year old boys and girls in Scotland, 2002–2010. (13th September 2011) - Levin, KA
Abstract : Background: The eating behaviour of children and adolescents is a priority area for the Scottish Government, as is tackling socioeconomic inequalities in health. Previous research has shown that eating behaviours and obesity in childhood are related to obesity and mortality in adulthood. Promoting good eating behaviour in adolescence therefore has long term benefits. Objective: The aim of this study is to describe changes in eating behaviour among adolescents living in Scotland between 2002 and 2010, to investigate socioeconomic inequalities in eating behaviour and changes in inequalities over time. Methods: Data from the 2002, 2006 and 2010 Health Behaviour in School-Aged Children survey were modelled using Multilevel Binomial modelling for 5 eating behaviour outcomes, adjusting for age, year, school type (state or independent) and the Family Affluence Scale (FAS). Results: For measures of daily fruit consumption and daily vegetable consumption, prevalence is higher among girls than boys, while daily consumption of chips is more prevalent among boys. While trends in vegetable and fruit consumption are not consistent, sweets, chips and crisps consumption decrease with time. Adjusting for age and sex, the odds of sweets consumption in 2010 are 0.48 (95% CI (0.43 to 0.53)), while the odds of crisps consumption are 0.37 (0.32, 0.41) and the odds of chips consumption are 0.35 (0.30, 0.42) that of 2002. Socioeconomic inequalities in eating behaviour are evident with higher prevalence of fruit and vegetable consumption and lower prevalence of sweets, crisps and chips consumption among children with high FAS relative to those with low FAS, for example, odds of a high FAS child eating crisps are 0.80 (0.72, 0.89) those of a low FAS child. When an interaction term between year and FAS are included, this is not significant for any of the five outcomes. FAS remains significant for all outcomes even after adjustment for family status, frequency of family meals, breakfast frequency and dieting behaviour. Variance at the school level remains significant for all models adjusting for these explanatory variables. Conclusions: Adolescent eating behaviour in Scotland has improved over time for some measures, while socioeconomic inequalities in eating behaviours have persisted with no significant change. This suggests that the reduction in crisps, chips and sweets consumption has occurred within all FAS groups. The key to improving the eating behaviour of adolescents may lie in school initiatives and/or food provision within schools.